TRIM5α: A Protean Architect of Viral Recognition and Innate Immunity - Spada, Stephanie J.; Grigg, Michael E.; Bouamr, Fadila; Best, Sonja M.; Zhang, Peijun (Viruses, 2024)
The evolutionary pressures exerted by viral infections have led to the development of various cellular proteins with potent antiviral activities, some of which are known as antiviral restriction factors. TRIpartite Motif-containing protein 5 alpha (TRIM5α) is a well-studied restriction factor of retroviruses that exhibits virus- and host-species-specific functions in protecting against cross-primate transmission of specific lentiviruses. This specificity is achieved at the level of the host gene through positive selection predominantly within its C-terminal B30.2/PRYSPRY domain, which is responsible for the highly specific recognition of retroviral capsids. However, more recent work has challenged this paradigm, demonstrating TRIM5α as a restriction factor for retroelements as well as phylogenetically distinct viral families, acting similarly through the recognition of viral gene products via B30.2/PRYSPRY. This spectrum of antiviral activity raises questions regarding the genetic and structural plasticity of this protein as a mediator of the recognition of a potentially diverse array of viral molecular patterns. This review highlights the dynamic evolutionary footprint of the B30.2/PRYSPRY domain in response to retroviruses while exploring the guided ‘specificity’ conferred by the totality of TRIM5α’s additional domains that may account for its recently identified promiscuity.